2018
DOI: 10.1055/s-0037-1617444
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Periorbital Edema and Ecchymosis after Rhinoplasty: Literature Review and Personal Approach

Abstract: Postoperative periorbital edema and ecchymosis are most bothersome to rhinoplasty patients. The degree of swelling and bruising is influenced by several factors, and numerous prophylactic and therapeutic measures have been described in the literature. This article reviews the current literature and concludes with the author's suggestions on how to best minimize postoperative periorbital edema and ecchymosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
(69 reference statements)
0
23
0
Order By: Relevance
“…The incisions were closed and a cast was applied to the dorsum for 4 days to prevent dislocation of the graft and to reduce ecchymosis and edema. 16 Eleven months postoperative outcome shows a widened nasal dorsum in the midline, reduced width, and bulbosity of the tip (►Fig. 2B, H).…”
Section: Case Studymentioning
confidence: 99%
“…The incisions were closed and a cast was applied to the dorsum for 4 days to prevent dislocation of the graft and to reduce ecchymosis and edema. 16 Eleven months postoperative outcome shows a widened nasal dorsum in the midline, reduced width, and bulbosity of the tip (►Fig. 2B, H).…”
Section: Case Studymentioning
confidence: 99%
“…Several studies encourage the use of local anesthesia, if they are applied approximately 15 minutes before the osteotomies. 26 Many studies have shown a reduction in edema and ecchymosis with the use of steroids, tranexamic acid, and intraoperative cooling. 13 A systematic review concludes that preoperative administration of tranexamic acid results in reduced intraoperative bleeding and postoperative edema and ecchymosis.…”
Section: Pre-and Intraoperative Carementioning
confidence: 99%
“…In clinical trials, various methods have been employed trying to reduce these side effects, which are summarized as employment of steroids, adrenaline solution one per 100,000, ice bag, intravenous tranexamic acid, clonidine, herbal material such as Arnica, and topical use of vitamins K. 4 Since the above agents are not impeccable either due to systemic effects or limitations in results of administration, if pharmacological agents can be used, which have easier and especially topical use and reduce effectively edema and ecchymosis, they can be routinely used in clinical settings. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 In clinical trials, various methods have been employed trying to reduce these side effects, which are summarized as employment of steroids, adrenaline solution one per 100,000, ice bag, intravenous tranexamic acid, clonidine, herbal material such as Arnica, and topical use of vitamins K. 4 Since the above agents are not impeccable either due to systemic effects or limitations in results of administration, if pharmacological agents can be used, which have easier and especially topical use and reduce effectively edema and ecchymosis, they can be routinely used in clinical settings. 4,5 Hirodoid (heparinoid or HPS) has anticlotting, fibrinolytic and anti-inflammatory effects, and until now, no study demonstrated the impact of hirodoid in reducing edema and ecchymosis following rhinoplasty, although other studies outside the field of surgery has been undertaken. 6 Hirodoid cream has an active compound called mucopolysaccharide polysulfate (MPS) which is a semi-synthetic molecule produced by the sulfation of a mixture of glycosaminoglycan derived from mammalian cartilage, with an average molecular weight of about 9700 Dalton.…”
mentioning
confidence: 99%